National initiatives to promote quality of care and patient safety: achievements to date and challenges ahead - Dalia Dreiher; Olga Blagorazumnaya; Ran Balicer; Jacob Dreiher (BMC, 2020)
Abstract Background The quality of healthcare in Israel is considered "high", and this achievement is due to the structure and organization of the healthcare system. The goal of the present review is to describe the major achievements and challenges of quality improvement in the Israeli healthcare system. Body In recent years, the Ministry of Health has made major strides in increasing the public's access to comparative data on quality, finances and patient satisfaction. Several mechanisms at multiple levels help promote quality improvement and patient safety. These include legislation, financial incentives, and national programs for quality indicators, patient experience, patient safety, prevention and control of infection and accreditation. Over the years, improvements in quality indicators, infection prevention and patient satisfaction can be demonstrated, but other fields show little change, if at all. Challenges and barriers include reluctance by unions, inconsistent and unreliable flow of information, the fear of overpressure by management and the loss of autonomy by physicians, and doubts regarding "gaming" of data. Accreditation has its own challenges, such as the need to adjust it to local characteristics of the healthcare system, its high cost, and the limited evidence of its impact on quality. Lack of interest by leaders, lack of resources, burnout and compassion fatigue, are listed as challenges for improving patient experience. Conclusion Substantial efforts are being made in Israel to improve quality of care, based on the use of good data to understand what is working and what needs particular attention. Government and health care providers have the tools to continue to improve. However, several mechanisms for improving the quality of care, such as minimizing healthcare disparities, training for quality, and widespread implementation of the "choosing wisely" initiative, should be implemented more intensively and effectively.